The use of tissue Doppler imaging in the assessment of diastolic dysfunction in children with chronic lung diseases - Iman H. Draz; Fatma El Zahraa Mostafa; Antoin F. AbdelMassih; Dalia El-Sayed; Rania El-Kaffas (Egyptian Pediatric Association Gazette, 2020)
Abstract Background Chronic lung diseases (CLD) in children such as bronchiectasis and interstitial lung disease represent a major public health problem with limited therapeutic options. These patients develop pulmonary hypertension (and core-pulmonale in severe cases) because of the recurrent hypoxia and chronic inflammation; which results in right heart enlargement and ventricular hypertrophy. The early identification and convenient treatment of diastolic dysfunction can prevent further complications of the disease including diastolic heart failure and death. We aim to demonstrate the usefulness of tissue Doppler imaging echocardiography (TDI) in the detection of subtle myocardial affection in interstitial lung disease and bronchiectasis as subgroups of (CLD) in children. We studied echocardiographic parameters of 40 pediatric patients with chronic lung disease using conventional M mode and tissue Doppler imaging and compared them with 40 healthy controls of matching age and sex distribution. Results Myocardial performance index (MPI) showed that 28 subjects had abnormal right ventricular (RV) MPI (10 with severe affection ≥ 0.6) and 21 subjects had abnormal LV MPI (11 severe affections ≥ 0.6). Thirty percent (30%) of the cases had affected lateral E/E' and 47.5% had affected septal E/E' when compared to controls. Grades of diastolic dysfunction were: 0, 1, 2, 3 in 18, 15, 6, and 1 patients, respectively. MPI LV and MPI RV showed statistically higher values in patients compared to controls (P < 0.001). Conclusion This study proved that TDI can accurately detect subtle myocardial dysfunction in pediatric CLD patients.